Un día de nieve - Keats, Ezra Jack. (New York : Puffin Books, 1991)
The adventures of a little boy in the city on a very snowy day.
K-3
Text in Spanish.
Translation of: The snowy day.
K-3
Keywords: Snow -- Juvenile fiction; African Americans -- Juvenile fiction; Cities and towns -- Juvenile fiction; Peter (Fictitious character : Keats) -- Juvenile literature; Snow -- Fiction; African Americans -- Fiction; Spanish language materials; Cities and towns -- Fiction; Peter (Fictitious character : Keats) -- Fiction; Snow -- Fiction; African Americans -- Fiction; Spanish language; Cities and towns -- Fiction; Peter (Fictional character : Keats) -- Fiction